The economy of the Bukidnon plateau during the American period - Lao, Mardonio M. (Philippine Studies, 1987)
This article is an attempt to trace the economic history of Bukidnon during the American colonial period. Three major economic trends during the period will be dealt with - foodcrop (rice and corn) production, cattle ranching, and pineapple growing. These topics will be discussed with the ultimate view of understanding the Bukidnon natives' participation in each of these economic trends and activities. Before touching on the main issues we shall take a look at the background that led to the American occupation.